2018
DOI: 10.1590/1807-1929/agriambi.v22n4p249-254
|View full text |Cite
|
Sign up to set email alerts
|

X-ray computed microtomography in the evaluation of the porous system of soils

Abstract: Analysis of shapes, sizes, continuity, orientation and irregularities of pores can help in the study of soil structural modifications induced by soil management. The study of the inter- and intra-aggregate porous space of urban and rural soils by tomographic images is the objective of this work. A morphometric characterization of the pores was carried out with the analysis of distribution of their size, shape and inclination in these two types of soil. The urban soil showed smaller percentage of inter-aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
2
1
0
2
Order By: Relevance
“…1). Similar results of a high contribution of complex pores to the overall porosity have also been previously measured for Brazilian soils (Ferreira et al, 2018;Borges et al, 2018;Costa et al, 2018;Pires et al, 2017;Passoni et al, 2015).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…1). Similar results of a high contribution of complex pores to the overall porosity have also been previously measured for Brazilian soils (Ferreira et al, 2018;Borges et al, 2018;Costa et al, 2018;Pires et al, 2017;Passoni et al, 2015).…”
Section: Resultssupporting
confidence: 88%
“…In terms of pore size distribution, the contribution of pores <10 mm to porosity was around 4% for F, 8% for ZT, 2% for CT and 3% for RT. This indicates that a large part of the porosity is composed of large inter-aggregate pores as observed by Costa et al (2018). Ferreira et al (2018) recently showed that >90% of porosity for a soil under ZT consisted of a main pore network as observed in our study.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As aplicações do equipamento na mecânica dos solos não saturados são várias, dentre as quais se pode destacar o cálculo das seguintes propriedades: densidade, porosidade, condutividade hidráulica, quebra das partículas e a curva de retenção (Al Mahbub;Haque, 2016). Costa et al (2018) realizaram o procedimento de tomografia computadorizada de raios X em Neossolo Regolítico Eutrófico (NRe), tipo de solo encontrado no agreste pernambucano. Na reconstrução das imagens obtidas no processo de escaneamento das amostras, foi possível identificar 28% de porosidade, da qual 27% são vazios interagregados, ou seja, são poros com grande conectividade, responsáveis pelo fluxo rápido de água no solo; e 1% de vazios intra-agregados, que são poros menores, com pequena conectivi-dade ou isolados, responsáveis por um fluxo mais lento de água e pelo seu armazenamento.…”
Section: Caracterização Microestruturalunclassified
“…Observaram um rearranjo de partículas acompanhado por uma reestruturação do espaço poroso quando alteradas as tensões hidráulicas. Isso ficou aparente a partir do fechamento de poros relacionados à estrutura do solo e à formação de novos poros.As aplicações do equipamento na mecânica dos solos não saturados são várias, dentre as quais se pode destacar o cálculo das seguintes propriedades: densidade, porosidade, condutividade hidráulica, quebra das partículas e a curva de retenção (Al Mahbub; Haque, 2016) Costa et al (2018). realizaram o procedimento de tomografia computadorizada de raios X em Neossolo Regolítico Eutrófico (NRe), tipo de solo encontrado no agreste pernambucano.…”
unclassified